Einstein's general theory of relativity : a concise introduction - Dolan, Brian P. (Cambridge: Cambridge University Press, 2023)
"This short text describes the physics of curved space-times and Einstein's general theory of relativity for physics undergraduates with a knowledge of advanced mechanics. It explains the physics of black holes, gravitational waves, the expanding Universe and the creation of the chemical elements in the Big Bang"--
Includes bibliographical references and index.
Keywords: General relativity (Physics)